Technology of Low Temperature Processing of Meat Ground Beef-Based Semi-Finished Products, Modified with Biological Supplement ‘Magnetofood’ - Yurchenko, Liubov I.; Tsikhanovska, Irina V.; Prikhodko, Elena Y. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(2): 190